Lighting Quality Affects Eyestrain of Operators at Sorting Station in Beverage Industry. (March 2017) - Anizar,; Erwin,
Abstract: This study observes sorters' performance in two beverage industries whose job is to separate defect products found. Sorters observe bottles quality and beverage quality continuously, therefore requiring more focused eyes which makes eyes' load heavier. Sorters' eyestrain causes more defect products pass the selection. In this study, measurement is conducted toward ilumintation, operators' time response, and defect products that pass the selection. Measurement is hold in 2 beverage industries for four days with four measurements per day, twice in the morning and twice in the afternoon. Ilumination is measured with 4 in 1 environmental meter in grid 1m x 1m, while operators' time response is measured with Flicker Fusion. Illuminance is generally higher in the morning than in the evening, but still under the standard of Indonesia. Overall, sorters' time response is higher in the morning than in the afternoon. Higher time response shows that operators experiencing lower fatigue than lower time response. The sorting duration also affects operators' time response and defect products which pass the selection.